2022
DOI: 10.3390/ijerph192013417
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activities and Learning Experience of Higher Education Students: Mediating Role of Quality of Life and Physical Self-Esteem

Abstract: The impacts of physical activities (PAs) on psychological and physical health consequences have been examined in both nonclinical and clinical contexts. Although PAs’ influences on physical consequences are regularly beneficial, the psychological positive impacts are less well-understood. This study investigates the effects of PA on physical consequences (i.e., physical self-esteem) and psychological and cognitive consequences (i.e., quality of life and learning experience). PA has been found to improve qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Moreover, the level of exerted PF among university students was higher before the pandemic than during the pandemic. These results are in line with [72], whose findings showed decreased physical fitness, academic performance, and overall quality of life among university students during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the level of exerted PF among university students was higher before the pandemic than during the pandemic. These results are in line with [72], whose findings showed decreased physical fitness, academic performance, and overall quality of life among university students during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…Very few studies have tried to understand the mediation roles played by PHS and ACD_PRF in the relationship between PHYS_FIT and QoL. PHS mediates the association between PHYS_FIT and QoL [84]. We were unable to find more previous studies that determined PHS' and ACD_PRF's mediation roles.…”
Section: The Mediation Role Of Physical Self-esteem (Phs) and Academi...mentioning
confidence: 84%
“…Students suffering from disturbed sleep quality or insomnia in a large group of 1279 university students was found to have a perceived stress at high level and physical and mental health related QoL at a low level (Carpi et al, 2022). Another study investigating the impacts of physical activities of adults on psychological and physical health outcomes indicated that physical activities support physical self-esteem, learning experience, and quality of life (Zayed & Elshaer, 2022). A review of longitudinal and cross-sectional studies researching the connection between bullying and health related QoL indicated that being bullied ends up with a dissatisfying health related QoL (Dubey et al, 2022).…”
Section: Introductionmentioning
confidence: 99%